Singing stone : a natural history of the Escalante Canyons - Fleischner, Thomas Lowe, 1954- (University of Utah Press, 1999)
Integrating personal narrative and natural history, Singing Stone is ideal for curious visitors to the Grand Staircase-Escalante National Monument as well as students of environmental studies.